Stereotactic Brainstem Biopsy: Technical Aspects with Emphasis on Role of Awake Craniotomy - Reddy Kanala Ramnadh; Krishna Yerramneni Vamsi; Thirumal Yerragunta; Kumar Vupuloori Arvind; Varshesh Shah (Indian Journal of Neurosurgery)
Introduction The role of frame-based stereotactic biopsy in brainstem lesions has been well established in literature. Transfrontal, transtentorial, and transcerebellar routes are used to access various targets within the brainstem. While the transfrontal approach is preferable in midbrain lesions, a transcerebellar approach via the middle cerebellar peduncle forms the shortest possible trajectory for pontine and medullary lesions. Objective Authors to describe the technical nuances of frame-based stereotactic biopsy of lower brainstem lesions to increase the procedural safety and efficacy. Materials and Methods Technical modifications in frame fixation were done to acheive the desired trajectory to the target. In adult cases biopsy was performed with patient awake during the procedure. Results Total of five patients underwent biopsy with the technical modifications. Three patients were adults and two were in pediatric age group. Their age ranged from 12 to 50 years. No complications were encountered. Two of the biopsies showed demyelination and the other three turned out to be low-grade glioma, pilocytic astrocytoma, and lymphoma, respectively. Conclusion Despite obvious inherent risks, the transcerebellar biopsy in semi-sitting position is a well-tolerated and effective method of obtaining a diagnostic tissue sample in brainstem lesions. We have noted that adoption of the technical modifications described in this article has aided in improving the safety and ease of the procedure.